Large Scale Experiments Representing a Containment Natural Circulation Loop during an Accident Scenario - R. Kapulla; G. Mignot; S. Paranjape; M. Andreani; D. Paladino (Science and Technology of Nuclear Installations)
The assessment of hydrogen release, distribution, and mitigation measures in the containment of a nuclear power plant is increasingly based on code calculations. These calculations require state-of-the-art experiments to benchmark the codes against them. Two of these experiments are presented in this paper. These experiments were conducted in the PANDA facility (Switzerland) in the framework of the OECD/NEA HYMERES project. The experiments consider natural circulation flow in a two-room type containment where flow loops can form between the inner and the outer zones. During normal operation these zones are separated and in the case of an accident they become either connected by the opening of rupture disks, convective foils, and dampers or connected by bursting of doors and opening of other connections between compartments. For the experiments considered here one lower PANDA-vessel represents the steam generator (SG) tower and the inaccessible area whereas the other vessel represents the outer room area. The lower vessels are isolated from one another except for a small aperture that represents the damper. The two upper vessels—representing the containment dome—are connected to the lower vessels through tubes. The scenario consisted of four phases. In phase 1, a high steam mass flow rate was injected in the vessel representing the SG tower. After the relaxation phase 2, helium (representing hydrogen) was injected in the same vessel (phase 3). Finally in phase 4 no active interventions were done until the end of the test. Two tests were conducted to evaluate the developing helium transport by the natural circulation flow: one with and one without damper (by closing the aperture). The results showed that a two-room containment (TRC) mixing scenario can be well represented with the PANDA facility. It is found that, with the mixing damper open, a global natural circulation loop develops over all four vessels, whereas with closed damper the natural circulation loop is established only between the three vessels representing the inner zone and the upper dome. It is shown that the presence of the damper has a strong effect on the resulting helium content in the inner zone with 3 times less helium at the end of the test compared with the configuration without damper. The formation of a stable helium stratification in the upper vessels was observed in the presence of the open damper.